Diabetes requiring insulin – recent developments in management. Issue 11 (18th June 2013) - Bennett, Katie; Joseph, Frank
Abstract Choice of insulin in the treatment of diabetes should be based on patient preference, lifestyle, blood glucose profile and risk of hypoglycaemia. Our Drug review focusses on key points and recent advances in the management of diabetes requiring insulin, followed by sources of further information and a review of the prescription data.